Optimal Multiproduct and Multiechelon Supply Chain Network Design - Montagna, Agustín Francisco (2018)
This work proposes a novel approach for the optimal design of multiproduct supply chain networks (SCN). Through a mixed integer linear programming (MILP) formulation the aim is to establish the structure of facilities that minimizes costs over the planning horizon, taking into account all the SCN's distinctive characteristics. We develop a generalized approach optimally determining the location of various types of facilities, multiproduct flows and demand fulfillment from any node in the network. This allows capturing the intertwined nature of decisions, leading to more efficient results. The proposed approach does not limit the number of echelons or layers. Instead, through a novel formulation, the optimal number of echelons is determined by the model, depending on the product to be supplied. To capture the economies of scale governing capital investments and operational costs, different types of facilities are proposed. Besides, the transportation expenses take different unitary costs according to the type of nodes being connected. Finally, the concept of waiting cost is introduced in order to capture the responsiveness of the SCN through the measurement of the time required to fulfill the clients? demands. A case study with different demand patterns and data structures is addressed to assess the potentials and efficiency of the SCN designs obtained with the proposed approach.